2022
DOI: 10.3389/fbioe.2022.808248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Platelet-Rich Plasma Therapy for Peripheral Nerve Regeneration: A Critical Review of Literature

Abstract: Peripheral nerve injury (PNI) is a common disease in clinic, and the regeneration process of peripheral nerve tissue is slow, and patients with PNI often suffer from the loss of nerve function. At present, related research on the mechanism of peripheral nerve regeneration has become a hot spot, and scholars are also seeking a method that can accelerate the regeneration of peripheral nerve. Platelet-rich plasma (PRP) is a platelet concentrate extracted from autologous blood by centrifugation, which is a kind of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…The exact molecular mechanisms by which PRP would reduce pain are not yet fully understood. Among them, the reduction in proinflammatory molecules and the resolution of inflammation, the upregulation of endocanabinoid receptors type 1 and 2, and the regeneration of axons and target reinnervation could be responsible [ 11 , 13 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact molecular mechanisms by which PRP would reduce pain are not yet fully understood. Among them, the reduction in proinflammatory molecules and the resolution of inflammation, the upregulation of endocanabinoid receptors type 1 and 2, and the regeneration of axons and target reinnervation could be responsible [ 11 , 13 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, platelet-rich plasma (PRP) infiltrations have emerged as an efficacious molecular intervention in patients with mild-to-moderate CTS or as adjuvant therapy to assist surgically repaired damaged nerves including the radial, ulnar, and median [ 3 , 4 , 6 , 7 , 8 , 9 , 10 , 11 ]. Different types of PRP—depending on their platelet concentrations, activation processes, and the presence or absence of leukocytes including leukocyte-rich plasma (L-PRP), platelet-rich fibrin (PRF) or plasma rich in growth factors (PRGF)—have emerged in the last few years for the treatment of neuropathies [ 12 , 13 ]. PRP has been applied as a liquid-to-gel product intraneurally and perineurally and/or by wrapping the repaired nerve area with a PRP matrix–like viscous and malleable membrane [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that PVRP gel is favorable for Schwann cells (SCs) and can effectively promote nerve regeneration (Ye et al, 2012). SCs are responsible for nerve cell proliferation and formation of migration bridges to the nerve stump (Wang et al, 2022). PVRP contains various growth factors (for example plateletderived growth factor -PDGF, transforming growth factor β -TGF β, vascular endothelial growth factor -VEGF, epidermal growth factor -EGF and insulin-like growth factor -IGF-1, special peptides, immune system messengers, enzyme inhibitors and other bioactive compounds (Arslan et al, 2022).…”
Section: Pvrp Preparation and Compositionmentioning
confidence: 99%
“…Moreover, plateletderived growth factor-BB (PDGF-BB) and IGF-1 may be the main cytokines affecting SC proliferation and migration. Vascular endothelium growth factor (VEGF) as a powerful angiogenic factor, released by macrophages, that is specific to the vascular endothelium, was shown to have chemotaxis effects, to promote axonal growth and neuronal survival(Wang et al, 2022). Also, its neuroprotective role was indicated due to positive effects on motor neuron survival and reduction of ischemic conditions(Hillenbrand et al, 2015) Pelletier et al (2015),.…”
mentioning
confidence: 99%
“…Researchers have started utilizing autologous therapies, such as platelet-rich plasma (PRP) and its variations, in the practice of regenerative medicine [ 22 ]. PRP is an autologous biological product enriched with a high concentration of growth factors and has been used to promote wound healing and tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%